High frequency of CD74 expression in lymphomas: implications for targeted therapy using a novel anti‐CD74‐drug conjugate. (8th October 2018) - Zhao, Shuchun; Molina, Arturo; Yu, Abigail; Hanson, Jeff; Cheung, Harry; Li, Xiaofan; Natkunam, Yasodha
Abstract: CD74 is a type II transmembrane glycoprotein that functions as an MHC class II chaperone and displays diverse roles in immune responses. Recently, anti‐CD74 immunotherapy has shown promise as an effective treatment strategy for lymphoid neoplasms in preclinical models. Using a human anti‐CD74 antibody (SP7219), we defined the expression of CD74 protein in both normal and over 790 neoplastic hematolymphoid tissue samples. We found that CD74 is expressed broadly in normal B‐cell compartments including primary and secondary lymphoid follicles and in the thymic medulla. The vast majority of lymphomas expressed CD74, including Hodgkin lymphomas (98%), B‐cell lymphomas (96%), extranodal NK/T‐cell lymphomas (88%), mature T‐cell lymphomas (80%), and plasma cell myeloma (75%). Our findings confirm and expand previous observations regarding the expression of CD74 and suggest that CD74 expression on tumor cells may be directly targeted for immunomodulatory therapy for lymphoid and plasma cell malignancies.